Salicylic Acid Priming Regulates Stomatal Conductance, Trichome Density and Improves Cadmium Stress Tolerance in Mentha arvensis L. - Zaid, Abbu; Mohammad, Firoz; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2022)
The application of phytohormones through seed priming could enhance quality of important medicinal and aromatic plants (MAPs) under heavy metal stress. We evaluated the potential of salicylic acid (SA) priming for overcoming the adverse effects of cadmium stress in Mentha arvensis L. plants. Suckers of plants were primed with SA before transplanting them into soil. At 30 days after transplanting, two doses (50 and 100 μm) of CdCl2 were applied to the soil. Both Cd treatments altered plant growth, photosynthetic pigments, leaf gas exchange attributes, and mineral nutrient contents. The 50 and 100 μm Cd treatments increased endogenous Cd content by 97.95 and 98.03%, electrolyte leakage (EL) by 34.21 and 44.38%, hydrogen peroxide (H2O2) by 34.71 and 55.80%, malondialdehyde (MDA) by 53.08 and 63.15%, and superoxide content (O2–•) by 24.07 and 38.43%, respectively. Cd triggered the up-regulation of antioxidant enzyme activities (superoxide dismutase, SOD; catalase, CAT; ascorbate peroxidase, APX; and glutathione reductase GR) and increased osmolyte biosynthesis and, interestingly, secondary metabolite (SM) accumulation. The presence of SA and Cd had an additive effect on these parameters. Nevertheless, plants primed with SA regulated stomatal conductance under Cd stress. SA priming to menthol mint plants under Cd stress overcome the effects of Cd stress while increasing SMs.